1974
DOI: 10.1128/jb.118.3.905-910.1974
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of One-Carbon Biosynthesis and Utilization in Escherichia coli

Abstract: The regulation of several enzymes involved in one-carbon metabolism was studied in a mutant of Escherichia coli K-12 defective in S-adenosylmethionine synthetase. The mutant that was reported to have a low endogenous concentration of S-adenosylmethionine had elevated levels of N-5, 10-methylene tetrahydrofolate reductase and serine transhydroxymethylase, but the level of N-5, 10methylene tetrahydrofolate dehydrogenase was not altered. These results suggest that S-adenosylmethionine plays a role in the regulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1

Year Published

1980
1980
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(21 citation statements)
references
References 24 publications
2
18
1
Order By: Relevance
“…A comparable increase is observed for f ( ' ) { a-Ser} under anaerobic growth conditions (Table 3), showing that the reversible cleavage of Ser is fast relative to the glycine cleavage in the anaerobic regime. This observation is in agreement with the finding that the Gly cleavage enzymes possess only about a tenth of the activity of serine hydroxymethyltransferase which catalyses Ser cleavage (Meedel and Pizer, 1974). Furthermore, Plamann et al (1983) have shown that the absence of a functional glycine cleavage pathway results in the excretion of Gly, thereby demonstrating its relevance for C, metabolism in the aerobic regime.…”
Section: Glycolysissupporting
confidence: 89%
“…A comparable increase is observed for f ( ' ) { a-Ser} under anaerobic growth conditions (Table 3), showing that the reversible cleavage of Ser is fast relative to the glycine cleavage in the anaerobic regime. This observation is in agreement with the finding that the Gly cleavage enzymes possess only about a tenth of the activity of serine hydroxymethyltransferase which catalyses Ser cleavage (Meedel and Pizer, 1974). Furthermore, Plamann et al (1983) have shown that the absence of a functional glycine cleavage pathway results in the excretion of Gly, thereby demonstrating its relevance for C, metabolism in the aerobic regime.…”
Section: Glycolysissupporting
confidence: 89%
“…Glycine is the substrate catalyzed by gcvP, and was reported to activate gcvTHP operon [28,35]. Nevertheless, our study indicated that supplemented glycine promoted gcvTHP expression in minimal media rather than LB.…”
Section: Discussioncontrasting
confidence: 61%
“…It was reported previously that the expression of gcvTHP operon can be induced by glycine in E. coli as well [28]. Therefore, to further investigate the correlation between gcvTHP expression and cas3 expression, the gcvTHP promoter was cloned into a reporter plasmid (pRCL2) and transformed into WT.…”
Section: The Cas3 and Gcvthp Promoter Activities Are Promoted By Glycinementioning
confidence: 99%
“…The new small RNA was discovered in the course of examining the promoter control region for the gcvA gene, encoding the transcriptional regulator of the glycine cleavage (Gcv) operon gcvTHP (Wilson et al, 1993). The Gcv enzyme system catalyses the oxidative cleavage of intracellular glycine to NH 3 , CO 2 and a one-carbon methylene group that is transferred to the acceptor tetrahydrofolate (Kikuchi, 1973;Meedel and Pizer, 1974). This reaction is a major source of the activated methyl compound 5,10-methylenetetrahydrofolate used in the biosynthesis of purines, thymine and methionine and its derivative S-adenosylmethionine, the donor substrate for many methyl transfer reactions (Mudd and Cantoni, 1964).…”
Section: Introductionmentioning
confidence: 99%